Program Kemitraan Masyarakat Bagi Kader Lansia Dengan Pelatihan Rom (Range Of Motion) Pasif Pada Tindakan Rehabilitatif Pasien Stroke Di Wilayah Kerja Puskesmas Bandung Kabupaten Tulungagung - ixora, Ixora ixora; Wulandari, Dewi; Niningasih, Rahayu (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2024)
Stroke is a non-communicable disease with cases that continue to occur increasing every year, appropriate treatment after a stroke really determines the patients maximum recovery rate. Until now, the incidence of stroke continues to increase, this is due to the lack of infotmation among post stroke patients about stroke care at home, most of them only get information regarding stroke nutrition, even though physically they also have to be trained, one of which is ROM (Range Of Motion) The result of a preliminary study at the puskesmas bandung in january 2022 showed an increase in the incidence of stroke. This community service activity aims to improve the knowledge and behavior of elderly cadres at the puskesmas bandung, with activities ranging from counseling about stroke and how to prevent stroke, socialization, ROM training for rehabilitation of post stroke patients, assistance with ROM training and evaluation of elderly posyandu cadres, Rehabititation program stroke, like ROM exercises, aims to be able to move joints as optimally and widely as possible according to a persons ability and not cause pain in the joints being moved. Movement in the joints will cause increased blood flow into the joint capsule. When the joint is moved, the surface of the cartilage between the two bones will rub against each other. Cartilage contains many proteoglycans attached to hyaluronic acid wich is hydrophilic. Pressure on the cartilage will force water out of the synovial matrix. If the pressure stops, the water that has escaped into the synovial fluid will be drawn back carrying nutrients from the fluid. Based on this description, what will be implemented in this community service is training for elderly cadres. Key Words: Stroke, Physical Exercises,ROM, Elderly